The impact of integrity on leadership effectiveness - Vakilbashi, Amin (2015)
Business Ethics is a vast title that contains so many subtitles underneath which each subtitle of these considered a field that can be practiced in our daily life. Integrity is one of these subtitles that goes under business ethics that is also plays an important role in our morals. By practicing integrity in leadership, it is considered one of the most significant implications that can have influence in our lives. Therefore, this integrity has an impact on leadership effectiveness in the human operations. This review paper aims to determine the relationship between integrity and leadership and how integrity can influence the effective of leadership. The main objective is to state the impact of integrity in leadership effectiveness by providing some theories from different articles. The authors of these articles have conducted many researches and surveys to prove their theories based on the topic and supported these theories using findings. The outcomes of these chosen articles were used to support the main objective of this review. It also discusses the perspectives of these authors and relates this discussion to the main topic of this review.